2013
DOI: 10.1021/es3041829
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ag Nanoparticle Exposure on p,p′-DDE Bioaccumulation by Cucurbita pepo (Zucchini) and Glycine max (Soybean)

Abstract: The effect of nanoparticle (NP), bulk, or ionic Ag exposure on dichlorodiphenyldichloroethylene (p,p'-DDE; DDT metabolite) accumulation by Glycine max L. (soybean) and Cucurbita pepo L. (zucchini) was investigated. The plants were grown in 125-mL jars of vermiculite amended with 500 or 2000 mg/L of bulk or NP Ag; ion controls at 5 and 20 mg/L were established. During 19 d of growth, plants were amended with solution containing 100 ng/mL of p,p'-DDE. Total shoot p,p'-DDE levels in non-Ag exposed G. max and C. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 39 publications
1
43
1
Order By: Relevance
“…Here we found that the combination of two distinct NPs at concentrations causing no or very limited cytotoxic effects when present alone led to a strong enhancement of toxicity. Potentiation phenomena have been described for a variety of chemicals in a number of systems (for instance studies of Smith et al (2013) in D. magna and Torre- Roche et al (2013) in C. pepo and G. max). However, few data are available on such effects after exposure to a mixture of NPs (Chen et al, 2008;Tang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we found that the combination of two distinct NPs at concentrations causing no or very limited cytotoxic effects when present alone led to a strong enhancement of toxicity. Potentiation phenomena have been described for a variety of chemicals in a number of systems (for instance studies of Smith et al (2013) in D. magna and Torre- Roche et al (2013) in C. pepo and G. max). However, few data are available on such effects after exposure to a mixture of NPs (Chen et al, 2008;Tang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have addressed the possible modulation of the activity of ions or chemicals by NPs. For instance, Tan et al (2012) showed that TiO 2 NPs enhance the uptake and retention of zinc and cadmium in Daphnia magna, and Torre- Roche et al (2013) demonstrated that exposure of Cucurbita pepo (zucchini) and Glycine max (soybean) to silver nanoparticles (AgNPs) leads to a significant reduction in the uptake of p,p′-DDE. However, with some exceptions (Guo et al, 2009;Tang et al, 2013), little attention has been given to the effects of co-exposure to ZnONPs and CuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, C 60 was found to increase the accumulation of dichlorodiphenyldichloroethylene (DDE; 30–65%) by several crop species when grown in vermiculite . Conversely, NP silver (Ag) coexposure generally suppressed DDE uptake (21–29%) by soybean grown in vermiculite; interestingly, the suppression was particle size–specific, with bulk Ag providing far less impact on pesticide accumulation . Similar conflicted data can be found in soil studies.…”
Section: Introductionmentioning
confidence: 66%
“…For instance, C 60 significantly increased weathered chlordane uptake from soil by Lycopersicon esculentum or Glycine max whereas MWCNTs decreased chlordane and DDx accumulation in Cucurbita pepo, Zea mays, Lycopersicum sculentum, and Glycine max (De La Torre-Roche et al, 2012a;Kelsey and White, 2013). Nanoparticle Ag was found to decrease the p,p′-DDE content of Glycine max tissues more than bulk Ag (De La Torre-Roche et al, 2012b). Although pharmaceutical contaminants and heavy metals in soils are currently not extensively tested in co-contamination studies, it is likely the co-existence of ENMs would affect their bioavailability, posing an important food safety concern.…”
Section: Impact On Co-existing Contaminantsmentioning
confidence: 95%